Colocando a prática de lembrar em prática: por aprendizagem móvel e em sala de aula - Souza, Roberta Ekuni de [UNIFESP] (2017)
Evidence-based education is advocated internationally. Two study techniques stand out to promote long lasting learning that are based on scientific data: a) retrieval practice, that is, trying to remember information which was previously encountered, also known as the testing effect; and b) distributed practice (spacing effect), or spacing study sessions rather than studying the content all at once, massively. However, in the international literature it is pointed out that students and teachers are generally unaware of these study techniques and tend to use ineffective strategies, showing that they are not used in educational settings. There are no data on demographic effects on the use of these techniques, nor how best to disclose them. It is also not known how best to apply these techniques in terms of the ideal spacing of repetition schemes to promote better learning, both in the classroom (classroom) and by mobile learning (m-learning) methods. Thus, in two experiments, our objectives were: a) to characterize the profile of study habits of Brazilian pre-college students and determine possible influences of gender and socioeconomic level; b) determine how best to disseminate these techniques, comparing the interest aroused by posts in social media in the form of texts, videos and the availability of a free application that employs these techniques; c) to analyze the improvement in the retention of information with repeated retrieval practices (2, 3 and 4 times) and with different spacing (1, 3 and 7 days) through mobile learning; and (d) to investigate the effects of retrieval practice in a naturalistic context (undergraduate subject with real content) in two moments (at the end of the classes in which the content was exposed or at the beginning of the next classes) and comparing retention of information to that elicited with instructor-led review with the same content in these two moments. We found that: a) pre-college students prefer inefficient study techniques as described internationally, regardless of their socioeconomic status, and that women use some techniques associated with less retention than men; b) the availability of free applications draw more interest than explanations and videos on the subject in social media and in person; c) that mobile learning involving recall and spacing practice improves learning to a greater extent after a single presentation of questions 1 and 3 days after the first presentation, and that this is maximized with 3 test presentations; d) in classrooms, a single test on each naturalistic content at the end of the class in which the content was taught leads to better retention (10%) than tests in the next class and instructor-led review at both placements. The data converge to the importance of encouraging students to use retrieval practice, which is possible through mobile learning, preferably 3 times, that a single attempt to remember information results in greater learning gain, especially when it occurs a short interval of days after the presentation of the content (both via application and in person).